Joint Evaluation of Employment Guarantee Scheme of Maharashtra PEO Pub No. 74 - Planning Commission (Planning Commission, 1977)
In Maharashtra’s Annual Plan for 1975-76, Rs. 40 crores were provided for implementing the State’s Employment Guarantee Scheme. At the time of discussions, the State Government invited the Planning Commission to send a team to undertake a Study of the projects taken up so far through the EGS and of those planned in 1975-76. Shri B. Sivaraman, Member, Planning Commission, accordingly visited the State in July 1975, and his Tour Report provided a framework for the implementation of the Scheme. 2. It was agreed at that lime, that the results of the working of the projects undertaken through the Employment Guarantee Scheme would be jointly evaluated, so that some feedback would be available in lime for the discussions for the Annual Plan for 1976-77. The PEO was called upon in August 1975, to initiate this work.
Field Report State Level Information Current Status Programme Evaluation Organisation Planning Commission Government of India New Delhi